Enterprise Profile and Women Owned Mitumba Enterprise Outcomes in Mombasa City Kenya - Chepchieng, Hillary; Nassiuma, Dr. Bernard Kibeti (International Journal of Entrepreneurship and Project Management, 2017)
Purpose: Entrepreneurial outcomes are influenced by networks which facilitate successful venture start-ups through reduction of the effects of contextual and process factors. Hence, personal entrepreneurial networks enhance successful Mitumba start-ups. The objectives of this study were to examine: The effects of enterprise profile on entrepreneurial outcomes: The effects of enterprise venture creation on enterprise outcomes, the influence of Social networks on enterprise outcomes and the utilization of network resources on entrepreneurial outcomes. Methodology: Descriptive survey was adopted in this study. The target population was 228 women entrepreneurs operating small enterprises in Mombasa city. A sample size of 114 entrepreneurs participated in this study. Results: The key results indicates that the majority of the predictors were significant and the internal consistency of instruments was reliable (Enterprise Venture Creation, Î± = 0.91and Social network, Î± = 0.971). Enterprise Venture creation had sig 0.359, hence, was not significant. A positive and significant association (p< 0.0144) was found on Utilization of Network resources. Enterprise profile had significance (.004), hence had an influence on mitumba outcomes. The Social network Intensity was significant (P< 0.000) the null hypothesis on Social network intensity was rejected. Conclusion and policy recommendation: This paper concludes that utilization of network resources as a predictor of Mitumba Enterprise Outcomes (MEO) was a strong predictor. The Social network Intensity supports Mitumba Enterprise Outcomes. While hence, venture creation was not supportive of Enterprise Outcomes.